The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/su11082415
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and Financial Capital in Chinese Cooperatives

Abstract: For the rural districts of China to get an economically and socially sustainable development, the strengthening of agricultural cooperatives is essential. This study aims at presenting a model about how social capital within the cooperatives can be converted into financial capital to the benefit of both the cooperative and the members. Case studies of four cooperatives serve as illustrations. There is a large amount of social capital in these cooperatives, with their operations simple enough to allow members t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
(44 reference statements)
1
15
0
Order By: Relevance
“…A decentralized, fine-grained structure of small-scale branches originally kept the bank close to its members, but over time its increasing size was accompanied by internal centralization and the loss of local autonomy. These results are consistent with the theoretical assumption that solving collective action problems is easier in smaller and relatively homogeneous groups and communities, as interaction is more direct, face-to-face and therefore of better quality (Olson, 1965; Douglas, 1986; Ostrom, 2004), which has been confirmed in studies on cooperatives (Fonteyne, 2007; Valentinov, 2007; Majee and Hoyt, 2010; Ruben and Heras, 2012; Jones et al , 2016; Yu and Nilsson, 2019). The empirical evidence, in our case, showed that the overall cooperative score on levels of organizational social capital increased where the size of the group decreased.…”
Section: Discussionsupporting
confidence: 84%
“…A decentralized, fine-grained structure of small-scale branches originally kept the bank close to its members, but over time its increasing size was accompanied by internal centralization and the loss of local autonomy. These results are consistent with the theoretical assumption that solving collective action problems is easier in smaller and relatively homogeneous groups and communities, as interaction is more direct, face-to-face and therefore of better quality (Olson, 1965; Douglas, 1986; Ostrom, 2004), which has been confirmed in studies on cooperatives (Fonteyne, 2007; Valentinov, 2007; Majee and Hoyt, 2010; Ruben and Heras, 2012; Jones et al , 2016; Yu and Nilsson, 2019). The empirical evidence, in our case, showed that the overall cooperative score on levels of organizational social capital increased where the size of the group decreased.…”
Section: Discussionsupporting
confidence: 84%
“…Finally, we provide additional evidence justifying the long-run sustainability of agricultural cooperatives. Recent literature has studied the enduring survivability of these organizations based on institutional theories, organizational adaptions, and social capital [33][34][35]. We argue that farm profitability is an especially useful proxy for sustainability, as it is a static indicator that considers both revenues and costs for producers.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 96%
“…While cooperatives with far-reaching horizontal and vertical integration may be more efficient due to economies of scale, this model does not seem to result in higher social capital within the membership [23]. When cooperatives begin to replicate the strategies of investor-owned firms, their members no longer feel as associated with them [10,22,24]. In turn, the geographical and social proximity among members, and between members and leadership appears to foster social capital [22].…”
Section: Introduction: Social Capital and Farming Cooperativesmentioning
confidence: 86%
“…The literature indicates how the performance of farming cooperatives is strongly affected by their ability to establish and maintain trust, confidence, and commitment among members [6]. For this reason, many authors agree that, since by design, agricultural cooperatives are network organisations formed with the motivation of mutual benefit and the expectation of collective actions among members, they are highly dependent on social capital [7][8][9][10][11]. In turn, lack of trust, reciprocal relationships, transparency, and other elements of social capital can lead to failure of the cooperative [11].…”
Section: Introduction: Social Capital and Farming Cooperativesmentioning
confidence: 99%